The problem of "Human and Power" in the modern political novel (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article analyzes the problem of personality clashes and political power in the novel. An attempt was made to study the peculiarities of the genre variety. Focuses on the author's vision of the political conflict in the novels «Floodplain» by V. Baranov and «Notes of a Ukrainian Madman» by L. Kostenko. Meaningful trends and prospects of development of genre variety in modern literary dynamics.